Legal implications of land fraud on security of tenure under the conveyancing law and practices in West Malaysia / Noraziah Abu Bakar - Abu Bakar, Noraziah (2019)
This research attempts to study how fraud affects the security of tenure in land transactions, in particular, the transfer of land and the creation of charge in favour of financial institutions. Other than the National Land Code 1965 (NLC), there is no specific statute that regulates the conveyancing practices in West Malaysia. Furthermore, the NLC merely deals with the procedural aspects of the conveyancing work. The conveyancing process begins with the preparation of documents, execution and attestation of documents, stamping of documents and finally, the presentation of documents at the relevant land office for registration. This thesis reveals that the existing conveyancing law and practices are not sufficient in providing the legal mechanisms to address the risk of fraud in land transactions. Such inadequacies have implications on the violation of security of tenure in conveyancing practices. This problem is the central argument of the thesis, which revolves around the inadequacies of the law and the impact on the security of tenure in the conveyancing system, since 'fraudulent land transactions deprive the registered owners and interest holders of valid titles or interests in land. The research employs a combination of a doctrinal and an empirical study. In the doctrinal analysis, the research analyses the primary and secondary data that include the NLC and case law, in order to examine the current legal framework in West Malaysia. This research uses the legal frameworks in New Zealand and Australia as benchmarks. In order to investigate the implications of land fraud on conveyancing practices, an empirical study is conducted which evidenced the inadequacies of the law in addressing the risk of fraud. The research finds that, despite the awareness of the risk of fraud in land cases, legal measures to reduce land fraud are still lacking. The study also reveals the existence of attempts to curb land fraud by implementing various administrative measures, but such initiatives are purely administrative in nature. Therefore, the thesis suggests several legal measures to be incorporated into the NLC in order to address the issue of land fraud, including introducing a verification regime in respect of the parties and documents, and imposing an immediate notification to the proprietors of any land transactions registered on the Register Document of Titles. As an interim measure against any attempt of land fraud, a special form of private caveat should be made available under the NLC to enable proprietors to protect land against any fraudulent activities. A compensation fund is an important aspect of the Torrens System] however, it was not inserted in the NLC during its introduction. Thus, as suggested by contemporary literature, it is pertinent to incorporate a compensation fund provision in the NLC in order to compensate for any loss arising from fraudulent land transactions. Alternatively, this thesis suggests that an insurance scheme be implemented and inserted into the NLC to ensure an immediate and effective compensation in the event of land fraud. This research is significant in assisting the policy makers in strengthening the conveyancing law and practices in order to reduce the risk of fraud. It also contributes to the body of knowledge and literature on conveyancing law and practices in West Malaysia.